Robust soil health monitoring systems: Why should we use them and what do they entail? - Accelerating Impacts of CGIAR Climate Research for Africa; CIFOR-ICRAF; CA4SH (2025)
This brief describes the need and policy context for monitoring soil health in Africa. It explains that a robust soil health monitoring system is more than data collection, it is an integrated platform and process with multiple functions. The brief also gives an overview of a well-designed soil health monitoring framework and examples of SMART (specific, measurable, achievable, relevant, time-bound) criteria.